Polish market of private banking. General characteristics and development trends - Górnik, Karolina (Polski rynek private banking. Ogólna charakterystyka i tendencje rozwoju, 2011)
The article presents the general characteristics and the development trends of the private banking market in Poland. The author’s analysis provides arguments to support the assertion of dynamic growth of the segment in Poland in the foreseeable future. Following Poland’s accession to EU structures and the liberalization of foreign exchange legislature, the share of private banking segment in the overall market of banking services in Poland will continue to grow
Ekonomia = Economics, 2011, Nr 2 (14), s. 299-308
Keywords: private banking/wealth management in Poland; Poland's liberalization of foreign exchange legislature; art banking services